TORREY, a Phase 2 study to evaluate the efficacy and safety of inhaled seralutinib for the treatment of pulmonary arterial hypertension. (1st November 2021) - Frantz, Robert P.; Benza, Raymond L.; Channick, Richard N.; Chin, Kelly; Howard, Luke S.; McLaughlin, Vallerie V.; Sitbon, Olivier; Zamanian, Roham T.; Hemnes, Anna R.; Cravets, Matt; Bruey, Jean‐Marie; Roscigno, Robert; et al.
Abstract : Aberrant kinase signaling that involves platelet‐derived growth factor receptor (PDGFR) α/β, colony stimulating factor 1 receptor (CSF1R), and stem cell factor receptor (c‐KIT) pathways may be responsible for vascular remodeling in pulmonary arterial hypertension. Targeting these specific pathways may potentially reverse the pathological inflammation, cellular proliferation, and fibrosis associated with pulmonary arterial hypertension progression. Seralutinib (formerly known as GB002) is a novel, potent, clinical stage inhibitor of PDGFRα/β, CSF1R, and c‐KIT delivered via inhalation that is being developed for patients with pulmonary arterial hypertension. Here, we report on an ongoing Phase 2 randomized, double‐blind, placebo‐controlled trial (NCT04456998) evaluating the efficacy and safety of seralutinib in subjects with World Health Organization Group 1 Pulmonary Hypertension who are classified as Functional Class II or III. A total of 80 subjects will be enrolled and randomized to receive either study drug or placebo for 24 weeks followed by an optional 72‐week open‐label extension study. The primary endpoint is the change from baseline to Week 24 in pulmonary vascular resistance by right heart catheterization. The secondary endpoint is the change in distance from baseline to Week 24 achieved in the 6‐min walk test. A computerized tomography sub‐study will examine the effect of seralutinib on pulmonary vascular remodelling. A separate heart rate monitoring sub‐study will examine the effect of seralutinib on cardiac effort during the 6‐min walk test.